Safety and long-term effectiveness of paroxysmal atrial fibrillation ablation with a contact force-sensing catheter: real-world experience from a prospective, multicentre observational cohort registry. Issue Volume 20:Issue FI 3(2018) (4th January 2018) - De Potter, Tom; Van Herendael, Hugo; Balasubramaniam, Richard; Wright, Matthew; Agarwal, Sharad C; Sanders, Prashanthan; Khaykin, Yaariv; Latcu, Decebal-Gabriel; Maury, Philippe; Pani, Antonio; Hayes, John; Kalman, Jonathan; et al.
Abstract: Aims: Real-time contact force (CF)-sensing radiofrequency ablation catheter for treatment of paroxysmal atrial fibrillation (PAF) allows optimization of electrode–tissue contact, which correlates with long-term success. This prospective, multicentre observational registry assessed the real-world clinical effectiveness of a CF-sensing catheter for ablation of drug-refractory PAF. Methods and results: Patients were followed-up at 3, 6, and 12 months after ablation. Outcome measures included isolation of targeted pulmonary veins (PVs) confirmed by entrance block (acute success), patient-reported freedom from symptomatic atrial fibrillation (AF) at 12 months (long-term effectiveness), Atrial Fibrillation Effect on Quality-of-life scores at 6 and 12 months, and incidence of predefined procedural complications. The registry enrolled 261 PAF patients (mean age 58.8 ± 11.3 years; 70.7% men; 91.7% Caucasian). Acute PV isolation was reported in 98.8% of patients [95% confidence interval (CI): 96.4–99.7%], and 12-month success for freedom from symptomatic AF was 75.7% (95% CI: 69.7–80.7%). Average CF for the evaluable cohort was 16.4 ± 3.9 g. There was a significant correlation between long-term effectiveness and stability of CF use [percentage of time CF was within investigator-selected working range; odds ratio (95% Wald CI), 1.0 (1.00–1.1); P = 0.030]. Average CF did not correlate with 12-month success. Clinically meaningful quality of life (QoL) improvements were observed at 6 and 12 months. Primary adverse events occurred in 2.7% patients. Conclusion: This observational registry showed that PAF ablation with a CF-sensing catheter had high acute success rates, favourable 12-month outcomes, and a good safety profile. Patients' QoL improved significantly. Long-term effectiveness significantly correlated with stable CF with adequate catheter–tissue contact (NCT01677052).